STRATEGY DEVELOPMENT OF BUSINESS LIVESTOCK BEEF CATTLE IN SUB-DISTRICT KULISUSU BARAT BUTON UTARA - Ismawati, Ismawati; Sani, Laode Arsad; Abadi, Musram (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
Sub-district Kulisusu Barat is one of the districts that can develop a beef cattle business, so a strategyis needed to utilize local resources. This study aimed to determine the process of creating a beef cattlebusiness in Sub-district Kulisusu Barat, Buton Utara Regency. Respondents were chosen deliberately(purposive sampling) by taking 20 respondents in each sample village based on respondents' criteriato have at least two beef cattle, livestock age of at least two years. The variables in this study wereinternal and external factors of livestock business development, including maintenance systems,raising method, the origin of the breed, sources of feed, water sources, production potential,reproductive potential, disease management and control, the experience of farmers, markets andmarketing, human resources and financial institutions. The results of the study were formulated thatthe strategy for developing beef cattle business includes the strength opportunities strategy (increasingthe scale of beef cattle business), the weakness opportunities strategy (improving the maintenance ofbeef cattle), the strength threats strategy (expanding the capacity of farmers and field officers), and theweakness strategy threats (improving marital management by utilizing IB technology).